(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3BNQgG (B:s
(3ef eGOI (B( (3MjQ (B) (3bhdg (B: (3bGd GdYLGL (B: (3JSeY ddLQY EPG GSJMjQG hGdMjQ HGdaJM THg GdMXjQg Ch GdMei cCfge bdHhG GdjGA CdaG ced GdSaQ GdChd ef cJGH hGdMeO ddg jJdhg ai GdKGfi aUd GdNGA ef HGH GdQGA s
(3JJab ai ChdgG eY Chd fSNI YGQa MceJ (B- 28 (3dZI HGNJdGa jSjQ LOkG ai HYV GdCdaGXs
(3fSNI KGefIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs